Election News Coverage and Entertaining Politics: A Content Analysis of Infotainment Characteristics in Canadian Newspapers’ Federal Election Coverage - Marinov, Robert N. (Université d'Ottawa / University of Ottawa, 2020)
Many scholars have noted the increasingly widespread combination of politically-relevant information and entertaining or sensational media formats and presentational styles over the past several decades, falling broadly under the umbrella term of ‘infotainment.’ However, in spite of this burgeoning infotainment literature very little research has been done on the nature and dynamics of infotainment within the Canadian context. This is especially true of research on infotainment within Canada’s traditional news media outlets. To being filling this gap, this study undertakes a mixed-methods content analysis of Canadian newspapers’ coverage of the 2019 federal election to evaluate the scope and nature of infotainment therein. Building off of a systematic review and mapping of the existing infotainment literature, this study develops a comprehensive conceptual and analytical framework for defining and evaluating infotainment characteristics within ‘hard news’ coverage. The quantitative and qualitative results are outlined in detail before being evaluated for their potential implications on citizens’ information processing and political knowledge, as well as some broader evaluations of potential implications for Canadian politics. These ethico-political considerations are developed by drawing on insights from a number of literatures, including political psychology and decision-making, strategic voting, and broader media and infotainment research.
Keywords: infotainment; political communication; electoral studies; news media